2000
DOI: 10.2527/2000.783675x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus bioavailability and digestibility of normal and genetically modified low-phytate corn for pigs.

Abstract: We conducted two studies to determine the bioavailability and apparent digestibility of P in a low-phytate corn hybrid (.28% total P, .10% phytate P) genetically modified to be homozygous for the 1pa1-1 allele and a nearly isogenic corn hybrid (normal) (.25% total P, .20% phytate P). Additionally, we conducted an in vitro assay involving a peptic and pancreatin digestion to estimate P availability. The first study used 50 individually penned pigs (initial body weight 9 kg) and 10 treatments in a randomized com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
68
0
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(92 citation statements)
references
References 0 publications
19
68
0
5
Order By: Relevance
“…Bone ash percentage was influenced (P<0.01) by aP levels (Table 2), increasing quadratically up to a maximum response of 0.520% (Figure 6). Similar results were found by O'Quinn et al (1997), Spencer et al (2000) and Hastad et al (2004) with pigs at different stages of production.…”
Section: Resultssupporting
confidence: 80%
“…Bone ash percentage was influenced (P<0.01) by aP levels (Table 2), increasing quadratically up to a maximum response of 0.520% (Figure 6). Similar results were found by O'Quinn et al (1997), Spencer et al (2000) and Hastad et al (2004) with pigs at different stages of production.…”
Section: Resultssupporting
confidence: 80%
“…However, the Linear Response Plateau model provided the best fit to the data, estimating at 0.328% the level of aP from which BA remained on a plateau (Figure 4). This result is consistent with those obtained by O'Quinn et al (1997), Spencer et al (2000) and Hastad et al (2004), who also found increase in the percentage of BA due to the increasing levels of aP in the diets of pigs at different stages of production.…”
Section: Resultssupporting
confidence: 82%
“…The mineral contents of the WS and WM grains (Table 6) were similar to previously reported values for sorghum: P (FAO, 1995;Glew et al, 1997), Fe (FAO, 1995Matuschek ,t al., 2001), Zn (FAO, 1995), Ca (FAO, 1995Kruger et al, 2013) and Mg (FAO, 1995;Glew et al, 1997), and maize: P (FAO, 1992;Spencer et al, 2000), Fe (FAO, 1992;Umeta et al, 2005), Zn (FAO 1992;Beiseigel et al, 2007;Mendoza et al, 1998;), Ca (FAO, 1992Mendoza et al, 2001;) and Mg (FAO, 1992;Mendoza et al, 2001). However, the mineral contents of the RTS and RNTS were higher than the reported ranges for sorghum.…”
Section: Effect Of Aqueous Soaking On the Mineral Contents And Phytatmentioning
confidence: 99%